Dilemmas in Participatory Approaches to Social Work - Gojová, Alice; Glumbíková, Kateřina (Participatory Social Work: Research, Practice, Education, 2019)
Both the community work and the participatory research can be understood as approaches used in social work that increase participants’ capacity to improve their lives and facilitate social change for the benefit of disadvantaged groups. In participatory approaches, dilemmas can arise, which are defined as a situation where a social worker faces two mutually exclusive choices, which he/she has to choose from. We also perceive dilemmas in both approaches as emerging in the interaction with the systems of values. The paper presents the findings from two research projects whose objectives included the identification of dilemmas from two areas, namely from community work and from a participatory approach to homeless mothers. The dilemmas are divided into two categories; from the perspectives of community workers and from a researcher’s point of view. To interpret data we used the theory of empowerment and the typology of power by the authors John French and Bertram Raven (1960). As part of the discussion, the paper provides an overview of dilemmas in participatory approaches to social work research, on the example of the above-mentioned projects.